Study the Information Seeking Actions in a Digital Engineering College Environment: Exploring information seeking in a digital engineering college environment (Journal of Advances and Scholarly Researches in Allied Education, 2021)
While it is one of the most often discussed topics in user research, the concept of informationseeking is seldom defined. People probably already know the term means what they believe it means,therefore they do this when they seek information. Seeking knowledge because one has a need to fulfillsome aim, as the definition of information-seeking puts it, suggests that the concept of informationseekingis more closely related to the idea of need than to the idea of information. The information needs,information-gathering routines, and information-seeking habits of online engineering students are theprimary focus of this study.